2018
DOI: 10.22260/isarc2018/0125
|View full text |Cite
|
Sign up to set email alerts
|

Automated Progress Monitoring of Masonry Activity Using Photogrammetric Point Cloud

Abstract: Information retrieval and automated progress estimation of ongoing construction projects have been an area of interest for researchers in the field of civil engineering. It is done using 3D point cloud asbuilt and as-planned model. Advancements in the field of photogrammetry and computer vision have made 3D reconstruction of buildings easy and affordable. But the high variability of construction sites, in terms of lighting conditions, material appearance, etc. and error-prone data collection techniques tend to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Presently, engineers and project managers monitor the working status of a construction labourer by looking at images (Braun, et al, 2015). Progress estimation is the comparison of planned schedules with as-built schedules or models to determine project progress (Pushkar, Senthilvel, and Varghese, 2018). In the stage following project estimation, data visualisation and reporting is performed to make the decision-making process smooth (Han and Fard, 2017).…”
Section: Progress Monitoring Stagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, engineers and project managers monitor the working status of a construction labourer by looking at images (Braun, et al, 2015). Progress estimation is the comparison of planned schedules with as-built schedules or models to determine project progress (Pushkar, Senthilvel, and Varghese, 2018). In the stage following project estimation, data visualisation and reporting is performed to make the decision-making process smooth (Han and Fard, 2017).…”
Section: Progress Monitoring Stagesmentioning
confidence: 99%
“…Pushkar, Senthilvel, and Varghese (2018), B -Omar andNehdi (2016), C -Meredith and Mantel (2009), D -Daniel, Kavgic, and Ergen (2019), E -Braun, et al (2015, F -Kim, Son, and Kim (2013), G -Fard, Mora, andSavarese (2015), H -Alizadehsalehi and Yitmen (2018), I -Fard and Peña-Mora (2007), J -Han and Fard (2017), K -Braun, et al (2020), L -Wang, et al (2021 …”
mentioning
confidence: 99%
“…There has been great interest in BIM-enabled autonomous mobile scanning systems in the construction field in recent years. Developments range from research projects [49][50][51] to startups launched on the market [52][53][54][55]. These usually involve using algorithms for object recognition and Scan-vs-BIM or Scan-to-BIM methods [49].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, CPM can be divided into several stages. Pushkar et al (2018), Omar and Nehdi (2016), Alizadehsalehi and Yitmen (2018) and Han and Fard (2017) have categorised CPM into four stages, namely, "Data acquisition", "Information retrieval", "Progress estimation and comparison" and "Results visualisation/reporting". Daniel et al (2019) and Fard et al (2009) have identified one more stage, namely, "Initial planning/Scheduling", in addition to the stages in CPM identified by the previous authors.…”
Section: Progress Monitoring Process In Construction Projectsmentioning
confidence: 99%
“…The authors explained that the collected data and information must be verified manually to ensure accurate verification. Progress estimation is the comparison of planned models with as-built models to determine progress discrepancies (Pushkar et al , 2018). In the stage following project estimation, data visualisation and reporting is performed to make a smooth decision-making process (Han and Fard, 2017).…”
Section: Literature Synthesismentioning
confidence: 99%